2014
DOI: 10.1136/jech-2014-204034
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the neighbourhood food environment on adiposity of low-income preschool-aged children in Los Angeles County: a longitudinal study

Abstract: Background Few studies have examined the association between the food environment and adiposity in early childhood, a critical time for obesity prevention. The objective of this study was to examine the longitudinal association between neighborhood food environment and adiposity among low-income preschool-aged children in a major metropolitan region in the United States. Methods The study sample was 32,172 low-income preschool-aged children in Los Angeles County who had repeated weight and height measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Grow et al (2010) found that children in low SES neighbourhoods have higher rates of childhood obesity. Neighbourhood factors such as unsafe areas that limit opportunities for exercise, low density of healthy food outlets and lack of available recreational facilities have been shown to contribute to the increase risk for childhood obesity (Borrell et al 2016;Chaparro et al 2014;Skinner & Foster 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Grow et al (2010) found that children in low SES neighbourhoods have higher rates of childhood obesity. Neighbourhood factors such as unsafe areas that limit opportunities for exercise, low density of healthy food outlets and lack of available recreational facilities have been shown to contribute to the increase risk for childhood obesity (Borrell et al 2016;Chaparro et al 2014;Skinner & Foster 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in one study the presence of convenience stores in neighborhoods was associated with 7-year-old girls’ excessive BMI-for-age growth over three years, but produce vendors and farmer’s markets were inversely associated with obesity risk [13]. However, a study based in Los Angeles County observed that children’s greater weight-for-height was associated with having healthy food outlets in the neighborhood [15]. An unmeasured factor is that the food outlet environment in neighborhoods may change over time, and children’s growth status could change with the dynamics of local food environment.…”
Section: Introductionmentioning
confidence: 99%
“…Given that individuals often travel farther than 1 mile to visit food establishments, researchers have challenged the use of neighborhoods defined by administrative units or buffers (7,8,11,1820). The objective of this study was to examine the relevance of different definitions of neighborhood food environments by quantifying individuals’ travel beyond commonly defined neighborhoods for food shopping or eating away from home.…”
Section: Introductionmentioning
confidence: 99%